The Representations about Gypsies in Russian Painting from XIXth to the Beginning of the XXth Centuries - Procop, Svetlana (Eikón / Imago, 2019)
The history of the Rom people, known as the Romaní people still needs important early evidence of their culture, artifacts, and iconography. These representations, in the reconstruction of its history, engraved in the works of art, are valuable information. Together with the ideas, images or objects discovered in the portraits and gender scenes, we obtain important data that can help support the reconstruction of traditions and customs, offering us important information as ethnological as anthropological. Ultimately, scientists stress the need to attract more attention in the true emotional demonstrations of writers and painters, reflected in their works, which have a special value.